Low-Carbohydrate Diets and Glycaemic Control in Type 1 Diabetes Mellitus - Michael Diamond (European Medical Journal Diabetes, 2018)
In recent years the successful treatment of Type 2 diabetes mellitus through total calorific and/or dietary carbohydrate restriction has been well established. The use of low-carbohydrate diets for the adjunctive management of Type 1 diabetes mellitus has been studied but to a lesser extent. Over the past 20 years, a growing body of evidence has examined the effects of daily carbohydrate restriction on the key markers of glycaemic control, including blood glucose variability, average daily blood glucose readings, and HbA1c. The majority of publications to date have demonstrated a beneficial impact of carbohydrate reduction on glycaemic control. Indeed, similar findings have also been replicated using diets restricted to foods with a low glycaemic index. Interestingly, following a low-carbohydrate diet can also uncover the hyperglycaemic effects of fat and protein consumption, and the clinical implications of this will be discussed within this review. There is evidence, however, to suggest that these diets can be difficult to adhere to and that they may even pose health risks to the patient. Acutely, they can cause hypo or hyperglycaemic events, potentiate the risks of ketosis, and deplete systemic glycogen stores. The long-term effects of a low-carbohydrate diet are not well documented; however, possible complications can include alterations in lipid profiles, micronutrient deficiencies, cardiac complications, and nephrolithiasis. This review presents an overview of the major studies to date that have looked at carbohydrate dietary manipulation and the subsequent impact on glycaemic control in populations with Type 1 diabetes mellitus.